Associations Among Child Abuse, Depression, and Interleukin-6 in Pregnant Adolescents: Paradoxical Findings. Issue 8 (October 2016) - Walsh, Kate; Basu, Archana; Werner, Elizabeth; Lee, Seonjoo; Feng, Tianshu; Osborne, Lauren M.; Rainford, Ashley; Gilchrist, Michelle; Monk, Catherine
ABSTRACT: Objective: Limited data exist on child abuse–related immune variation during pregnancy, despite implications for maternal and infant health and extensive data showing that abuse history and depression are related to increased inflammation in other populations. This study examined associations among child abuse, depression, circulating levels of inflammatory markers, and perinatal health in pregnant adolescents, a group at high risk for childhood abuse and poor birth outcomes. Methods: Pregnant teenagers ( n = 133; 14–19 years; 89.5% Latina) reported on abuse and depression and had two blood draws (24–27 and 34–37 gestational weeks, second and third trimesters, respectively) for interleukin-6 (IL-6) and C-reactive protein; birth outcomes were collected. Results: Abuse and depression interacted to predict higher IL-6 at second trimester ( B = 0.006, p = .011) such that severely abused adolescents with high depression had higher IL-6 relative to severely abused adolescents with low depression; depression did not differentiate IL-6 levels for those with low abuse severity. Abuse and IL-6 also interacted to predict gestational age at birth ( B = 0.004, p = .040) such that those with low abuse and high IL-6 and those with high abuse and low IL-6 had infants with earlier gestational age at birth. Cortisol at the second trimester mediated the association between IL-6 and gestational age at birth (indirect effect estimate=−0.143, p < .039). Conclusions: Depression severity distinguished IL-6 levels among more severely abused pregnant Latina adolescents, but it was unrelated to IL-6 among less severely abused adolescents. Cortisol explained the relationship between IL-6 and earlier gestational age at birth. Multiple adversities and inflammation may influence birth outcomes and potentially affect intergenerational health.